Association of the antidepressants and the periodontal status: An original research - Rizleena Majeed; Krishna V Sathi; Ruthika S Patil; Neetu Singh; Shilpa Duseja; Kameswari Kondreddy (Wolters Kluwer Medknow Publications, 2024)
Antidepressants have anti-inflammatory effects and boost immunity, and dentists should be aware. This case-control study included only those patients who consented to take part and had a ham-d score of at least 16 and a diagnosis of moderate-to-severe depression. Inclusion criteria included adults, those experiencing moderate to severe depression, taking fluoxetine or venlafaxine, and those with twenty or more teeth. Exclusion criteria included tobacco chewers, smokers, women expecting or nursing, periodontal treatment, antibiotics, anti-inflammatory medication, or vitamin/nutritional supplements. Patients who had had surgery or other therapy were excluded from the study. Three groups of patients were created: Control, venlafaxine, and fluoxetine. A periodontist assisted in the dental examination, and indices were observed. The analysis was done using Statistical Package for the Social Sciences (SPSS) version 24.0. Number, percentage, mean, and standard deviation were used to present the values. Results showed that antidepressants may be a risk factor for periodontal health, with increased periodontal parameters, and concluded that It is crucial to frequently check the periodontal health of depressed people using fluoxetine or venlafaxine since these drugs put good periodontal tissues at risk.